If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 27 + -4 = x Combine like terms: 27 + -4 = 23 23 = x Solving 23 = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 23 + -1x = x + -1x Combine like terms: x + -1x = 0 23 + -1x = 0 Add '-23' to each side of the equation. 23 + -23 + -1x = 0 + -23 Combine like terms: 23 + -23 = 0 0 + -1x = 0 + -23 -1x = 0 + -23 Combine like terms: 0 + -23 = -23 -1x = -23 Divide each side by '-1'. x = 23 Simplifying x = 23
| -18=-8v-v | | 25=7-4x | | -8x^2+48x+576=0 | | 1=1-2x+5x | | 3n-2-4n=-2 | | 8x+12x=2200 | | 4x+8x=2200 | | 5/2c=35/3 | | -log(x+9)-log(x-9)=-2log | | -21=5x-5+4 | | -u/7=-25 | | X=y^2-10y-25 | | 8x-7-8x=4 | | 2x-16y=8 | | A+14=14 | | -12=5p+p | | (j-2)/2j | | 3(v+5)-10=-13 | | 2x+5=x-2.5 | | 3+2*6-4=32 | | 0=4.9x^2+4x-10 | | -6=p-4p | | 7.50x-3.50x+15=95 | | 3(w-8)=-33 | | -.5=cos(pi•t/6) | | 1/x-3/4=x/1 | | 49=6u-17 | | 4l-12=8+5l | | -4t-3t=28 | | 5+0.65p=12.3 | | 3y=-2x-8 | | 3(x+5)=6x-21 |